Method for preparing wind driven generator conductor by using Cu-Cr-Zr-Ag-Ti material
By performing solid solution quenching, cold pulling and aging treatment on Cu-Cr-Zr-Ag-Ti alloy, the problem of poor strength and high-temperature softening performance of wind turbine conductor materials is solved, and high strength and fatigue resistance are achieved wind turbine conductor.
Patent Information
- Application Number
- CN202411602442.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing Cu-Cr-Zr-Ag-Ti materials have problems with poor strength and poor resistance to high temperature softening in wind turbine conductor applications.
By insulating Cu-Cr-Zr-Ag-Ti alloy rod material at 900-1000°C for 0.5-1 hour, after being subjected to solid solution quenching in water, followed by cold drawing and aging treatment, a softening with high strength and high temperature resistance was prepared. Performance wind turbine conductors.
The high strength, high temperature softening and fatigue resistance of wind turbine conductors are achieved, and the comprehensive performance of materials is improved.
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of advanced metal processing, and in particular relates to a method for preparing a wind generator conductor by using Cu-Cr-Zr-Ag-Ti material. Background Art
[0002] As wind turbines become increasingly important, higher requirements are placed on the performance of wind turbine transmission conductor materials. Cu-Cr-Zr-Ag-Ti materials not only have dispersed precipitation of fine Cr phase reinforcement, but also further add Ag. The addition of Ag forms complex precipitates of CuAgZr, which form coherent and semi-coherent dispersed fine precipitates with the matrix, further increasing the strength of the material, reducing the sensitivity of the material to cracks, and greatly improving the high temperature softening performance. At the same time, Ag has less impact on the matrix material than Zr. On this basis, rare earth elements are added to reduce material impurities while further refining the grains, further improving the strength and high temperature softening resistance of the material, and increasing the trial life.
[0003] At present, the newly added onshore wind power tender models are mainly 5 MW and above. Since the second half of 2022, many leading offshore wind power companies have launched models of 15 MW and above. In July this year, a single 16 MW unit was connected to the grid for power generation. However, the current Cu-Cr-Zr-Ag-Ti material has problems with poor strength and poor resistance to high temperature softening.
[0004] The reliability of wind turbine motor transmission conductors must also be safer and more efficient than before, which places higher demands on materials. Summary of the invention
[0005] In view of the problems of poor strength and poor high-temperature softening resistance of Cu-Cr-Zr-Ag-Ti materials in the prior art, the purpose of the present invention is to provide a method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti materials. The wind turbine conductor prepared by the method has high strength, high-temperature softening resistance and fatigue resistance.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material comprises the following steps: The Cu-Cr-Zr-Ag-Ti alloy rod is kept at 900-1000°C for 0.5-1h and then solution quenched in water; then cold drawing and aging treatment are performed to obtain a wind turbine conductor.
[0007] Furthermore, the cold drawing steps are: firstly, 4-7 passes of first drawing are performed, then an intermediate annealing treatment is performed, then 4-7 passes of second drawing are performed, and finally annealing is performed under the protection of an argon atmosphere.
[0008] Furthermore, the maximum diameter of the first drawing is reduced by 2-4 mm in sequence, until it reaches 32-72 mm.
[0009] Furthermore, the temperature of the intermediate annealing treatment is 800-900° C., and the holding time is 0.5-3 h.
[0010] Furthermore, the annealing temperature under the protection of argon atmosphere is 400-500° C., and the holding time is 1-2 hours.
[0011] Furthermore, the aging treatment temperature is 350-450°C and the time is 4-6h.
[0012] Further, the Cu-Cr-Zr-Ag-Ti alloy bar is prepared by the following process: CuCr, CuAg, CuZr and CuTi master alloys and electrolytic copper plates are melted according to the weight percentage of Cu-(0.5~2)wt.%Cr-(0.05~0.3)wt.%Zr-(0.1~0.5)wt.%Ag-(0.05~0.3)wt.%Ti, and allowed to stand. During the standing process of the solution, (0.05-0.3)wt.%Ce is added to the solution and stirred, and then cast into ingots; the ingots are hot rolled and cold rotary forged, and then hot extruded.
[0013] Furthermore, the hot rolling temperature is 800-900°C and the time is 0.5-1h.
[0014] Furthermore, the hot extrusion temperature is 800-950° C. and the time is 0.5-1 h.
[0015] A wind turbine conductor has a tensile strength of 440-485 MPa, a resistivity of 2.0-2.1 uΩ·cm, a softening temperature of 550-590°C, and a yield strength of 350-385 MPa.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The Cu-Cr-Zr-Ag-Ti material of the present invention not only has the fine Cr phase reinforcement of dispersion precipitation, but also further adds Ag, and the addition of Ag forms a complex precipitate of CuAgZr, which forms a coherent and semi-coherent dispersed fine precipitate phase with the matrix, further increases the material strength, reduces the sensitivity of the material to cracks, and greatly improves the high temperature softening resistance. At the same time, Ag has a smaller impact on the matrix material than Zr. On this basis, the inexpensive rare earth element Ce is added to reduce the material impurities while further refining the grains, further improving the strength and high temperature softening resistance of the material, and improving the service life. In the present invention, by adding alloy components, more beneficial strengthening phases are precipitated in the alloy matrix, and the strength and high temperature softening resistance are improved, while the fatigue resistance is greatly improved; in the present invention, by solution annealing, cold drawing and aging treatment, the comprehensive performance of the wind turbine conductor, such as electrical conductivity, thermal conductivity, strength, softening resistance and fatigue resistance, is excellent.
[0017] The wind generator conductor prepared by the invention has a tensile strength of 440-485 MPa, a resistivity of 2.0-2.1 uΩ·cm, a softening temperature of 550-590°C, and a yield strength of 350-385 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Describe all the drawings and reference numerals involved in the invention, such as: Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION
[0019] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0020] The chemical composition and weight percentage of the Cu-Cr-Zr-Ag-Ti alloy in the present invention are: Cu-(0.5-2) wt.%Cr-(0.05-0.3) wt.%Zr-(0.1-0.5) wt.%Ag-(0.05-0.3) wt.%Ti.
[0021] See also Figure 1 The present invention provides a method for preparing a wind turbine conductor using a Cu-Cr-Zr-Ag-Ti material, comprising the following steps: (1) Vacuum melting High-purity CuCr, CuAg, CuZr, and CuTi master alloys are prepared by specific vacuum melting equipment, and the impurity content of the raw materials is not more than 0.01%. The master alloy and high-purity electrolytic copper plate are then melted according to the weight percentage of Cu-(0.5~2)wt.%Cr-(0.05~0.3)wt.%Zr-(0.1~0.5)wt.%Ag-(0.05~0.3)wt.%Ti, and allowed to stand. During the standing process, (0.05-0.3)wt.%Ce is added to the solution, and then electromagnetic stirring is performed for 30 minutes, and the solution is cast into ingots with a diameter of 330-365mm and a length of 1.5-3m. There are no obvious defects such as looseness and shrinkage on the surface of the bar; (2) Sawing, cold forging and hot rolling After keeping at 800-900℃ for 0.5-1h, the bar is rolled to 280-300mm, the surface of the ingot is turned by lathe to 1-2mm, and then cold forged to 250-280mm. The length after sawing is not less than 200mm, and the bar with no surface cracks is obtained; (3) Hot extrusion The rod is heated to 800-950℃, kept warm for 0.5-1h, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 70-80mm. The flat strip surface has no defects, and the rod head and tail are cut off to obtain Cu-Cr-Zr-Ag-Ti alloy rods; (4) Online solution annealing The Cu-Cr-Zr-Ag-Ti alloy rod is heated, kept at 900-1000°C for 0.5-1h, and then solution quenched in water; (5) Cold drawing Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, draw 4-7 times, and the maximum diameter is reduced by 2-4mm successively until it reaches 32-72mm. Use a common solid solution box furnace for intermediate annealing. The annealing temperature is 800-900℃, and the insulation time is 0.5-3h. After grinding, draw 4-7 times again, and change the diameter by 0.5-2mm successively until the maximum diameter reaches 18-70mm. Anneal under argon atmosphere protection. The annealing temperature is 400-500℃, and the insulation time is 1-2h. After the surface is polished with a scouring pad, it is drawn 1-2 times, and finally a flat strip with a maximum diameter of 16-68mm is drawn. (6) Timeliness treatment Under atmosphere protection, aging treatment is carried out at 350-450℃ for 4-6h, and then the steel is straightened and cut into fixed sizes.
[0022] (7) Sawing, bending, and punching First, use a high-speed sawing machine to cut the edges, and the sawing feed rate is 0.1-0.5m / s; enter the corresponding position and quantity according to the requirements, and then the holes can be punched automatically; select the bending mold R3-R9, and according to the material thickness and working angle, the system automatically calculates the front limit distance 0-50mm, and sets the processing starting point, and then normal bending can be performed; (8) Polishing Grind the surface as required, the roughness Ra is not greater than 25, and then pack it after grinding.
[0023] Specific examples are given below.
[0024] Example 1 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloy and the high-purity electrolytic copper plate according to the weight percentage of Cu-0.6wt.%Cr-0.06wt.%Zr-0.3wt.%Ag-0.1wt.%Ti, smelt the ingredients, let stand, add 0.05wt.%Ce during the solution standing, and then stir electromagnetically for 30 minutes, and cast into a rod blank with a diameter of 330mm and a length of 1.5m, and the surface of the rod has no obvious defects such as looseness and shrinkage holes; Step 2: The bar blank is kept at 800℃ for 1h and then rolled to a diameter of 280mm. The surface of the ingot is turned by lathe to 1-2mm and then cold forged to a diameter of 250mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks. Step 3: The bar without surface cracks is heated to 850°C, kept warm for 1 hour, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 70 mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar, keep it at 900°C for 1 hour, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 4 passes of drawing are performed, and the maximum diameter is reduced by 2mm in sequence until it reaches 32mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 800℃ and the insulation time is 3h. After grinding, 4 more passes of drawing are performed, and the diameter is reduced by 0.5mm in sequence until the maximum diameter reaches 18mm. Annealing is performed under argon atmosphere protection. The annealing temperature is 400℃ and the insulation time is 2h. The surface is polished with a scouring pad and then drawn once, and finally a flat strip with a maximum diameter of 16mm is drawn; Step 6: Perform aging treatment at 400℃ for 4h under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0025] Step 7: Use a sawing feed rate of 0.5m / s for sawing; enter the corresponding position and quantity as required to perform automatic punching; select bending die R9, and the system automatically calculates the front limit distance of 30mm according to the material thickness and working angle. Set the processing starting point and perform normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0026] Example 2 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloys and high-purity electrolytic copper plates according to the weight percentage of Cu-0.3wt.%Cr-0.06wt.%Zr-0.3wt.%Ag-0.1wt.%Ti, smelt the ingredients, and let the solution stand. During the standing process, 0.3wt.%Ce is added and electromagnetically stirred for 30 minutes, and then cast into a rod blank with a diameter of 365mm and a length of 2m. The surface of the rod has no obvious defects such as looseness and shrinkage holes; Step 2: The bar blank is kept at 900℃ for 0.5h and then rolled to a diameter of 300mm. The surface of the ingot is lathe-turned by 1-2mm and then cold-forged to a diameter of 270mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks. Step 3: The bar without surface cracks is heated to 850°C, kept warm for 1 hour, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 80 mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar at 900°C, keep it at this temperature for 1 hour, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 5 passes of drawing are performed, and the maximum diameter is reduced by 3mm in sequence until it reaches 72mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 820℃ and the insulation time is 2.5h. After grinding, 5 more passes of drawing are performed, and the diameter is reduced by 1mm in sequence until the maximum diameter reaches 70mm. Annealing is performed under argon atmosphere protection. The annealing temperature is 500℃ and the insulation time is 1h. The surface is polished with a scouring pad and then drawn twice, and finally a flat strip with a maximum diameter of 60mm is drawn; Step 6: Perform aging treatment at 400℃ for 4h under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0027] Step 7: Use a sawing feed rate of 0.5m / s for sawing; enter the corresponding position and quantity as required to perform automatic punching; select bending die R9, and the system automatically calculates the front limit distance of 30mm according to the material thickness and working angle. Set the processing starting point and perform normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0028] Example 3 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloys and high-purity electrolytic copper plates according to the weight percentage of Cu-0.6wt.%Cr-0.06wt.%Zr-0.3wt.%Ag-0.1wt.%Ti, smelt the ingredients, and let the solution stand. During the standing process, 0.1wt.%Ce is added and electromagnetically stirred for 30 minutes, and then cast into a rod blank with a diameter of 340mm and a length of 3m. The surface of the rod has no obvious defects such as looseness and shrinkage holes; Step 2: The bar blank is kept at 850°C for 0.7h and then rolled to a diameter of 290mm. The surface of the ingot is turned by lathe to 1-2mm and then cold forged to a diameter of 280mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks; Step 3: The bar without surface cracks is heated to 900°C, kept warm for 1 hour, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 75mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar at 900°C, keep it at this temperature for 1 hour, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 6 passes of drawing are performed, and the maximum diameter is reduced by 4mm in sequence until it reaches 40mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 850℃ and the insulation time is 2h. After grinding, 7 passes of drawing are performed again, and the diameter is reduced by 2mm in sequence until the maximum diameter is 40mm. Annealing is performed under argon atmosphere protection. The annealing temperature is 450℃ and the insulation time is 1.5h. The surface is polished with a scouring pad and then drawn once, and finally a flat strip with a maximum diameter of 30mm is drawn; Step 6: Perform aging treatment at 400℃ for 6 hours under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0029] Step 7: Use a sawing feed rate of 0.5m / s for sawing; enter the corresponding position and quantity as required to perform automatic punching; select bending die R9, and the system automatically calculates the front limit distance of 30mm according to the material thickness and working angle. Set the processing starting point and perform normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0030] Example 4 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloy and the high-purity electrolytic copper plate according to the weight percentage of Cu-0.6wt.%Cr-0.06wt.%Zr-0.3wt.%Ag-0.1wt.%Ti, smelt the ingredients, let stand, add 0.2wt.%Ce during the solution standing, and then stir electromagnetically for 30 minutes, and cast into a rod blank with a diameter of 350mm and a length of 2.5m, and the surface of the rod has no obvious defects such as looseness and shrinkage holes; Step 2: The bar blank is kept at 830°C for 0.8h and then rolled to a diameter of 295mm. The surface of the ingot is turned by lathe to 1-2mm and then cold forged to a diameter of 260mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks; Step 3: The bar without surface cracks is heated to 850°C, kept warm for 1 hour, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 70 mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar at 950°C, keep it at this temperature for 1 hour, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 7 passes of drawing are carried out, and the maximum diameter is reduced by 2mm successively until it reaches 50mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 900℃ and the holding time is 0.5h. After grinding, 7 more passes of drawing are carried out, and the diameter is reduced by 2mm successively until the maximum diameter is 40mm. Annealing is carried out under the protection of argon atmosphere. The annealing temperature is 450℃ and the holding time is 1.5h. The surface is polished with a scouring pad and then drawn once, and finally a flat strip with a maximum diameter of 30mm is drawn; Step 6: Perform aging treatment at 400℃ for 5h under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0031] Step 7: Use a sawing feed rate of 0.5m / s for sawing; enter the corresponding position and quantity as required to perform automatic punching; select bending die R9, and the system automatically calculates the front limit distance of 30mm according to the material thickness and working angle. Set the processing starting point and perform normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0032] Example 5 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloys and high-purity electrolytic copper plates according to the weight percentage of Cu-0.6wt.%Cr-0.06wt.%Zr-0.3wt.%Ag-0.1wt.%Ti, smelt the ingredients, and let the solution stand. During the standing process, 0.3wt.%Ce is added and electromagnetically stirred for 30 minutes, and then cast into a rod blank with a diameter of 360mm and a length of 3m. The surface of the rod has no obvious defects such as looseness and shrinkage holes; Step 2: The bar blank is kept at 800℃ for 1h and then rolled to a diameter of 285mm. The surface of the ingot is lathe-turned by 1-2mm and then cold-forged to a diameter of 255mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks. Step 3: The bar without surface cracks is heated to 850°C, kept warm for 1 hour, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 80 mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar at 900°C, keep it at this temperature for 1 hour, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 4 passes of drawing are performed, and the maximum diameter is reduced by 3mm successively until it reaches 60mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 870℃ and the insulation time is 1h. After grinding, 4 more passes of drawing are performed, and the diameter is reduced by 0.5mm successively until the maximum diameter reaches 50mm. Annealing is performed under the protection of argon atmosphere. The annealing temperature is 470℃ and the insulation time is 1.2h. The surface is polished with a scouring pad and then drawn once, and finally a flat strip with a maximum diameter of 16-68mm is drawn; Step 6: Perform aging treatment at 450℃ for 4h under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0033] Step 7: Use a sawing feed rate of 0.5m / s for sawing; enter the corresponding position and quantity as required to perform automatic punching; select bending die R9, and the system automatically calculates the front limit distance of 30mm according to the material thickness and working angle. Set the processing starting point and perform normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0034] Example 6 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloys and high-purity electrolytic copper plates according to the weight percentage of Cu-0.5wt.%Cr-0.05wt.%Zr-0.5wt.%Ag-0.2wt.%Ti, smelt the ingredients, and let the solution stand. During the standing process, 0.05wt.%Ce is added and electromagnetically stirred for 30 minutes, and then cast into a rod blank with a diameter of 330mm and a length of 2m. The surface of the rod has no obvious defects such as looseness and shrinkage holes; Step 2: The bar blank is kept at 800℃ for 1h and then rolled to a diameter of 280mm. The surface of the ingot is turned by lathe to 1-2mm and then cold forged to a diameter of 250mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks. Step 3: The bar without surface cracks is heated to 900°C, kept warm for 0.5h, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 70mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar, keep it at 900°C for 1 hour, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 4 passes of drawing are performed, and the maximum diameter is reduced by 2mm in sequence until it reaches 32mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 800℃ and the insulation time is 3h. After grinding, 4 more passes of drawing are performed, and the diameter is reduced by 0.5mm in sequence until the maximum diameter reaches 18mm. Annealing is performed under argon atmosphere protection. The annealing temperature is 400℃ and the insulation time is 2h. The surface is polished with a scouring pad and then drawn once, and finally a flat strip with a maximum diameter of 16mm is drawn; Step 6: Perform aging treatment at 450°C for 6 hours under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0035] Step 7: Use a sawing feed rate of 0.4m / s for sawing; enter the corresponding position and quantity as required to perform automatic punching; select bending mold R3, and the system automatically calculates the front limit distance of 10mm according to the material thickness and working angle. Set the processing starting point and perform normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0036] Example 7 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloys and high-purity electrolytic copper plates according to the weight percentage of Cu-2wt.%Cr-2wt.%Zr-0.1wt.%Ag-0.3wt.%Ti, smelt the ingredients, let stand, add 0.1wt.%Ce during the solution standing, and then stir electromagnetically for 30 minutes, and cast into a rod blank with a diameter of 330mm and a length of 1.5m, and the surface of the rod has no obvious defects such as looseness and shrinkage holes; Step 2: The bar blank is kept at 800℃ for 1h and then rolled to a diameter of 300mm. The surface of the ingot is turned by lathe to 1-2mm and then cold forged to a diameter of 280mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks. Step 3: The bar without surface cracks is heated to 850°C, kept warm for 0.7h, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 70mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar, keep it at 1000°C for 0.5h, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 4 passes of drawing are performed, and the maximum diameter is reduced by 2mm in sequence until it reaches 32mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 800℃ and the insulation time is 3h. After grinding, 4 more passes of drawing are performed, and the diameter is reduced by 0.5mm in sequence until the maximum diameter reaches 18mm. Annealing is performed under argon atmosphere protection. The annealing temperature is 400℃ and the insulation time is 2h. The surface is polished with a scouring pad and then drawn once, and finally a flat strip with a maximum diameter of 16mm is drawn; Step 6: Perform aging treatment at 350°C for 4 hours under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0037] Step 7: Use a sawing feed rate of 0.3m / s for sawing; enter the corresponding position and quantity as required, and then punch holes automatically; select bending die R5, and the system automatically calculates the front limit distance of 40mm according to the material thickness and working angle. Set the processing starting point, and then perform normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0038] Example 8 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloy and the high-purity electrolytic copper plate according to the weight percentage of Cu-1wt.%Cr-0.3wt.%Zr-0.2wt.%Ag-0.1wt.%Ti, smelt the ingredients, let stand, add 0.2wt.%Ce during the solution standing, and then stir electromagnetically for 30 minutes, and cast into a rod blank with a diameter of 330mm and a length of 1.5m, and the surface of the rod has no obvious defects such as looseness and shrinkage holes; Step 2: The bar blank is kept at 800℃ for 1h and then rolled to a diameter of 280mm. The surface of the ingot is turned by lathe to 1-2mm and then cold forged to a diameter of 250mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks. Step 3: The bar without surface cracks is heated to 830°C, kept warm for 0.8h, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 70mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar, keep it at 950°C for 0.7h, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 4 passes of drawing are performed, and the maximum diameter is reduced by 2mm in sequence until it reaches 32mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 800℃ and the insulation time is 3h. After grinding, 4 more passes of drawing are performed, and the diameter is reduced by 0.5mm in sequence until the maximum diameter reaches 18mm. Annealing is performed under argon atmosphere protection. The annealing temperature is 400℃ and the insulation time is 2h. The surface is polished with a scouring pad and then drawn once, and finally a flat strip with a maximum diameter of 16mm is drawn; Step 6: Perform aging treatment at 380°C for 5 hours under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0039] Step 7: Use a sawing feed rate of 0.2m / s for sawing; enter the corresponding position and quantity as required to perform automatic punching; select bending die R8, and according to the material thickness and working angle, the system automatically calculates the front limit distance of 20mm, sets the processing starting point, and then performs normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0040] Example 9 Step 1: prepare high-purity CuCr, CuAg, CuZr, and CuTi master alloys through a specific vacuum melting device, wherein the impurity content of the raw materials is not more than 0.01%, and then mix the master alloy and the high-purity electrolytic copper plate according to the weight percentage of Cu-1.5wt.%Cr-1wt.%Zr-0.4wt.%Ag-0.05wt.%Ti, smelt the ingredients, let stand, add 0.3wt.%Ce during the solution standing, and then stir electromagnetically for 30 minutes, and cast into a rod blank with a diameter of 330mm and a length of 1.5m, and there is no obvious looseness, shrinkage holes and other defects on the surface of the rod; Step 2: The bar blank is kept at 800℃ for 1h and then rolled to a diameter of 280mm. The surface of the ingot is turned by lathe to 1-2mm and then cold forged to a diameter of 250mm. The length after sawing is not less than 200mm to obtain a bar with no surface cracks. Step 3: The bar without surface cracks is heated to 800°C, kept warm for 1 hour, and then conveyed into the extrusion cylinder by a conveyor belt for large diameter positive hot extrusion deformation to form a flat strip, with the maximum diameter reduced to 70 mm. The flat strip has no defects on the surface, and the rod head and tail are cut off to obtain a Cu-Cr-Zr-Ag-Ti alloy bar; Step 4: Heat the Cu-Cr-Zr-Ag-Ti alloy bar, keep it at 920°C for 1 hour, and then solution quench it in water; Step 5: Use a 3-5 ton hydraulic automatic drawing machine to continuously change the diameter and cold draw deformation. First, 4 passes of drawing are performed, and the maximum diameter is reduced by 2mm in sequence until it reaches 32mm. Use an ordinary solid solution box furnace for intermediate annealing. The annealing temperature is 800℃ and the insulation time is 3h. After grinding, 4 more passes of drawing are performed, and the diameter is reduced by 0.5mm in sequence until the maximum diameter reaches 18mm. Annealing is performed under argon atmosphere protection. The annealing temperature is 400℃ and the insulation time is 2h. The surface is polished with a scouring pad and then drawn once, and finally a flat strip with a maximum diameter of 16mm is drawn; Step 6: Perform aging treatment at 430℃ for 6 hours under atmosphere protection, and cut into fixed sizes for packaging after straightening.
[0041] Step 7: Use a sawing feed rate of 0.1m / s for sawing; enter the corresponding position and quantity as required to perform automatic punching; select bending die R6, and the system automatically calculates the front limit distance of 50mm according to the material thickness and working angle. Set the processing starting point and perform normal bending; Step 8: Polish the surface as required, roughness Ra25, and pack after polishing.
[0042] The performance of the wind power generation conductors of Examples 1-5 is shown in Table 1.
[0043] Table 1 Performance of Examples 1-5
[0044] It can be seen from Table 1 that the wind turbine conductor prepared by the present invention has a tensile strength of 440-485 MPa, a resistivity of 2.0-2.1 uΩ·cm, a softening temperature of 550-590° C., and a yield strength of 350-385 MPa.
[0045] The development of the wind turbine conductor in the present invention, i.e., the high-strength and high-conductivity copper alloy for wind turbine generator sets, has gone through three stages: the first stage, low-strength and high-conductivity, during which the main purpose is to add elements such as Ag, Cd, As, Te, Rb and other elements that do not significantly reduce the conductivity of the copper alloy to the copper alloy for alloying. The conductivity of the alloy elements obtained in this way can reach 90% IACS, but the mechanical performance index is not ideal and cannot meet the use requirements. It is mainly a one-element or two-element alloy system design, which is mainly used to meet the use of low-power wind turbine generator sets; the second stage, medium-strength and medium-conductivity, the design idea during this period is to increase the strength of the alloy by slightly sacrificing part of the conductivity, explore the method of multi-element alloying and combining subsequent heat treatment to improve the alloy performance, and obtain both mechanical and electrical properties. The medium-strength and medium-conductivity copper alloys, typical alloy systems include Cu-Cr-Zr alloys, which are mainly used to meet the needs of mid-range power wind turbines; the third stage, high strength and high conductivity, this stage begins to re-explore the types of added elements, focusing on the development of complex multi-element alloy systems, mainly developing materials containing Cr, Zr, Ag, Ni, Si, Mg, Sn, Zn, RE, Ce, Ti and other elements, and focusing on improvement and innovation in processing technology. The main research is to form a supersaturated solid solution through solid solution treatment while adding alloy elements. The supersaturated solid solution can be precipitated in the form of a precipitated phase during subsequent aging, thereby achieving the purpose of strengthening. Through such treatment, the strength and conductivity of copper can be maintained at a high level, which is mainly to prepare for the higher power of wind turbines in the future.
[0046] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material, characterized in that: The following steps are involved: The Cu-Cr-Zr-Ag-Ti alloy rod is kept at 900-1000°C for 0.5-1h and then solution quenched in water; then cold drawing and aging treatment are performed to obtain a wind turbine conductor.
2. The method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material according to claim 1, characterized in that: The steps of cold drawing are: firstly, 4-7 passes of first drawing are performed, then intermediate annealing is performed, then 4-7 passes of second drawing are performed, and finally annealing is performed under the protection of argon atmosphere.
3. The method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material according to claim 2, characterized in that: The maximum diameter of the first drawing is reduced by 2-4 mm to 32-72 mm.
4. The method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material according to claim 2, characterized in that: The temperature of the intermediate annealing treatment is 800-900°C, and the holding time is 0.5-3h.
5. The method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material according to claim 2, characterized in that: The annealing temperature under argon atmosphere protection is 400-500°C, and the holding time is 1-2h.
6. The method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material according to claim 1, characterized in that: The temperature of aging treatment is 350-450℃ and the time is 4-6h.
7. The method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material according to claim 1, characterized in that: Cu-Cr-Zr-Ag-Ti alloy bars are produced by the following process: CuCr, CuAg, CuZr and CuTi master alloys and electrolytic copper plates are melted according to the weight percentage of Cu-(0.5~2)wt.%Cr-(0.05~0.3)wt.%Zr-(0.1~0.5)wt.%Ag-(0.05~0.3)wt.%Ti, and allowed to stand. During the standing process of the solution, (0.05-0.3)wt.%Ce is added to the solution and stirred, and then cast into ingots; the ingots are hot rolled and cold rotary forged, and then hot extruded.
8. The method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material according to claim 1, characterized in that: The hot rolling temperature is 800-900°C and the time is 0.5-1h.
9. The method for preparing a wind turbine conductor using Cu-Cr-Zr-Ag-Ti material according to claim 1, characterized in that: The temperature of hot extrusion is 800-950°C and the time is 0.5-1h.
10. A wind turbine conductor prepared according to the method according to any one of claims 1 to 9, characterized in that: The wind turbine conductor has a tensile strength of 440-485 MPa, a resistivity of 2.0-2.1 uΩ·cm, a softening temperature of 550-590°C, and a yield strength of 350-385 MPa.